Optimization of Problem Based Learning Model in Thematic Learning in Elementary Schools - Yunianto, Teguh; Nur Hidayati, Atika; Maya Sari, Tri; Qiftiyah, Maratul (EDUCARE: Journal of Primary Education, 2024)
Implementing problem-based learning in elementary schools is challenging, as it requires a lack of teacher understanding and training and time and technology constraints. A dense curriculum also limits the effectiveness of PBL. Nevertheless, PBL can improve students' critical, collaborative, and analytical thinking skills. This study used a qualitative descriptive design to explore implementing the Problem-Based Learning model in thematic learning, focusing on its stages, challenges, and success factors. Data were collected through observation, interviews, and document analysis, with triangulation to ensure validity. Ethical standards such as obtaining informed consent and maintaining confidentiality were upheld. The results of this study indicate that implementing Problem-Based Learning in Islamic elementary schools, including elementary school, strengthens student competencies through active, collaborative, and problem-based learning. This method enhances students' social skills, teamwork, critical thinking, and independence while motivating them through interactive media. Educators are facilitators, assisting students in organizing information and developing creative solutions. Although challenges such as high costs and longer implementation times pose obstacles, adequate infrastructure support and positive student responses make PBL effective in equipping them with essential life skills for the future. This study's contribution is to illustrate that the application of the Problem-Based Learning model in Islamic elementary schools is effective in improving student competencies through active, collaborative, and problem-oriented learning activities. This study also shows that PBL can improve students' social skills, teamwork, critical thinking, and independence and motivate them with the use of interactive media.